Characterizing the cytoprotective activity of Sarracenia purpurea L., a medicinal plant that inhibits glucotoxicity in PC12 cells - Harris, Cory S; Asim, Muhammad; Saleem, Ammar; Haddad, Pierre S; Arnason, John T; Bennett, Steffany A (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background The purple pitcher plant, Sarracenia purpurea L., is a widely distributed species in North America with a history of use as both a marketed pain therapy and a traditional medicine in many aboriginal communities. Among the Cree of Eeyou Istchee in northern Québec, the plant is employed to treat symptoms of diabetes and the leaf extract demonstrates multiple anti-diabetic activities including cytoprotection in an in vitro model of diabetic neuropathy. The current study aimed to further investigate this activity by identifying the plant parts and secondary metabolites that contribute to these cytoprotective effects. Methods Ethanolic extracts of S. purpurea leaves and roots were separately administered to PC12 cells exposed to glucose toxicity with subsequent assessment by two cell viability assays. Assay-guided fractionation of the active extract and fractions was then conducted to identify active principles. Using high pressure liquid chromatography together with mass spectrometry, the presence of identified actives in both leaf and root extracts were determined. Results The leaf extract, but not that of the root, prevented glucose-mediated cell loss in a concentration-dependent manner. Several fractions elicited protective effects, indicative of multiple active metabolites, and, following subfractionation of the polar fraction, hyperoside (quercetin-3-O-galactoside) and morroniside were isolated as active constituents. Phytochemical analysis confirmed the presence of hyperoside in the leaf but not root extract and, although morroniside was detected in both organs, its concentration was seven times higher in the leaf. Conclusion Our results not only support further study into the therapeutic potential and safety of S. purpurea as an alternative and complementary treatment for diabetic complications associated with glucose toxicity but also identify active principles that can be used for purposes of standardization and quality control.